Capacidad de un consorcio nitrificante para Biotransformar la Ampicilina - Ramírez Muñoz, José Juan (Universidad Autónoma Metropolitana, 2018)
The emerging organic contaminants (EOCs) comprise a broad set of compounds that include metabolites and transformation products, present in the environment in amounts of ng to mg. Within the EOCs, there are drugs, personal care products, pesticides, etc. More than half of the antibiotics produced worldwide are beta-lactams and many of them have been detected in effluents from sewage treatment plants, including ampicillin. The presence of antibiotics in the aquatic environment is of concern and may contribute to bacterial resistance, and also the synergistic effect that may exist with other pollutants present in the environment on human health and ecosystems is unknown. The pollution of water by nitrogen is mainly due to the presence of ammonium in wastewater, and its elimination in treatment plants is mainly carried out through biological processes such as nitrification and denitrification. Studies on the biotransformation of ampicillin by nitrifying sludge and the effect of this antibiotic on nitrification are scarce. The objective of this work was to evaluate the capacity of a nitrifying culture for the biotransformation of ammonium and ampicillin in batch cultures, as well as to evaluate the effect of this antibiotic on the nitrifying process. The study of the physiological and kinetic behavior of the nitrifying consortium in the presence of ampicillin (10, 25 and 50 mg/L) was carried out using response variables such as consumption efficiencies, yields and specific rates. As a source of inoculum for batch cultures, a continuous stirred tank reactor with nitrifying sludge, physiologically stable was used (ENH4+ (%) de 99.9 ± 0.1; Y (mg N/mg NH4+-N consumed) nitrate: 0.77 ± 0.06; nitrite: 0.02 ± 0.02 and microbial biomass: 0.04 ± 0.01). Under the experimental conditions and ampicillin concentrations of 10, 25 and 50 mg/L, no effect on efficiency (E = 99.7 ± 4.2%) and yields (YNO2- = 0, YNO3- = 1.0 ± 0.1 mg N/mg N-NH4+ consumed) of the nitrifying process was observed as the sludge behavior was very similar in the controls without ampicillin and the assays with antibiotic. Like the physiological behavior of the consortium, the kinetics of nitrifying respiration also did not have significant changes in the presence of ampicillin. The specific rates of both ammonium oxidation and nitrate formation were similar between control cultures and cultures with antibiotic, showing that ampicillin did not cause an inhibitory effect on nitrification either. Overall, the results obtained from efficiencies, yields and specific rates provide clear evidence that ampicillin up to 50 mg/L did not affect the physiology or kinetics of the nitrifying respiratory process. The elimination of ampicillin in the cultures was mainly attributed to the processes of biosorption (adsorption on the sludge) (23.2 to 47.0%) and biotransformation (10.0 to 29.8%) and to a lesser extent to physical-chemical processes (16.0 to 16.5%). At the three initial concentrations of ampicillin added, a remnant of antibiotic was observed after 24 h of culture (26.9 to 34.1%), obtaining an average efficiency of 70.5 ± 2.5%. After 94 h of culture, the antibiotic (25 mg/L) could be eliminated up to 79.3%. The low consumption of ampicillin after 24 h could probably be related to a limitation of dissolved oxygen (2.0 ± 0.1 mg DO/L) and/or the pH value of 5.8. With the increase in the initial concentration of antibiotic, there was a greater participation of the sludge in the biotransformation process of ampicillin and at the same time an increase in the specific rate of ampicillin consumption. These results show that the sludge was able to oxidize ammonium to nitrate by nitrification and eliminate ampicillin biologically. The nitrifying sludge showed the ability to transform ampicillin, but without reaching full mineralization. Given that no alteration of the nitrifying process was observed in the presence of ampicillin, it is possible to rule out the participation of nitrifying bacteria in the biotransformation of ampicillin and to suggest the participation of the consortium's heterotrophic microflora; Los contaminantes orgánicos emergentes (EOC: emerging organic contaminants) comprenden un amplio conjunto de compuestos en los que se incluyen metabolitos y productos de transformación, presentes en el ambiente en cantidades de ng a mg. Dentro de los EOC, se encuentran fármacos, productos de cuidado personal, pesticidas, etc. Más de la mitad de los antibióticos producidos mundialmente son betalactámicos y muchos de ellos se han detectado en los efluentes de las plantas de tratamiento de aguas residuales, entre ellos la ampicilina. La presencia de antibióticos en el medio acuático es preocupante ya que pueden contribuir a la resistencia bacteriana, y además se desconoce el efecto sinérgico que puede haber con otros contaminantes presentes en el medio sobre la salud humana y los ecosistemas. La contaminación del agua por nitrógeno se da principalmente por la presencia de amonio en aguas residuales y su eliminación en las plantas de tratamiento se lleva a cabo a través de procesos biológicos como la nitrificación y la desnitrificación. Los estudios sobre la biotransformación de la ampicilina por lodos nitrificantes y el efecto de este antibiótico sobre la nitrificación son escasos. El objetivo de este trabajo fue evaluar la capacidad de un cultivo nitrificante para la biotransformación de amonio y ampicilina en cultivos en lote, así como evaluar el efecto de este antibiótico sobre el proceso nitrificante. Se realizó el estudio del comportamiento fisiológico y cinético del consorcio nitrificante en presencia de ampicilina (10, 25 y 50 mg/L) usando variables de respuesta como eficiencias de consumo, rendimientos y velocidades específicas. Como fuente de inóculo para los cultivos en lote, se empleó un reactor en continuo de tanque agitado con lodo nitrificante, fisiológicamente estable (ENH4+ (%) de 99.9 ± 0.1; Y (mg N/mg N-NH4+ consumido) de nitrato: 0.77 ± 0.06; de nitrito: 0.02 ± 0.02 y de biomasa microbiana: 0.04 ± 0.01). Bajo las condiciones experimentales y a las concentraciones de ampicilina de 10, 25 y 50 mg/L, no se observó efecto alguno sobre la eficiencia (E = 99.7 ± 4.2%) y los rendimientos (YNO2- = 0, YNO3- = 1.0 ± 0.1 mg N/mg N-NH4+ consumido) del proceso nitrificante, comportándose el lodo en los controles sin ampicilina y los ensayos con antibiótico de forma muy similar. Al igual que el comportamiento fisiológico del consorcio, la cinética de la respiración nitrificante tampoco sufrió cambios significativos en presencia de ampicilina. Las velocidades específicas tanto de oxidación de amonio como de formación de nitrato fueron similares entre los cultivos control y los cultivos con antibiótico, mostrando que la ampicilina tampoco provocó un efecto inhibitorio en la nitrificación. En conjunto los resultados obtenidos de eficiencias, rendimientos y velocidades específicas aportan evidencias claras de que la ampicilina hasta 50 mg/L no afectó ni la fisiología ni la cinética del proceso respiratorio nitrificante. La eliminación de ampicilina en los cultivos se dio principalmente a través de los procesos de biosorción (adsorción en el lodo) (23.2 a 47.0%) y de biotransformación (10.0 a 29.8%) y en menor medida a través de procesos físico-químicos (16.0 a 16.5%). A las tres concentraciones iniciales de ampicilina adicionada, se observó un remanente de antibiótico después de 24 h de cultivo (26.9 a 34.1%), obteniéndose una eficiencia promedio de 70.5 ± 2.5%. Despues de 94 h de cultivo, el antibiótico (25 mg/L) pudo ser eliminado hasta un 79.3%. El bajo consumo de ampicilina después de 24 h pudo probablemente estar relacionado con una limitación de oxígeno disuelto (2.0 ± 0.1 mg OD/L) y/o el valor de pH de 5.8. Con el incremento en la concentración inicial de antibiótico, hubo una mayor participación del lodo en el proceso de biotransformación de la ampicilina y a la vez un aumento en la velocidad específica de consumo. Estos resultados muestran que el lodo fue capaz de oxidar amonio a nitrato por nitrificación y eliminar ampicilina por vía biológica. El lodo nitrificante mostró capacidad de transformar la ampicilina, pero sin llegar a la mineralización completa. Dado que no se observó alteración alguna del proceso nitrificante en presencia de ampicilina, se pudo descartar la participación de las bacterias nitrificantes en la biotransformación de la ampicilina y sugerir la participación de la microflora heterótrofa del consorcio